Preparation and application of low metal ion high acetalization degree polyvinyl acetal resin
Patent Information
- Application Number
- CN202611189165.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]针对现有技术的不足,本发明提供了低金属离子高缩醛化度聚乙烯醇缩醛树脂的制备及应用,解决了现有聚乙烯醇缩醛树脂因内部残余金属离子产生物理交联导致溶液粘度偏高,难以同时兼顾高缩醛化度带来的耐水耐醇性能与制备高固含油墨所需的低粘度流动性的问题
1、本发明通过将聚乙烯醇与脂肪族醛在酸催化下反应,使树脂的缩醛化度达到75%至85%,较高比例的缩醛结构增加了高分子链的疏水基团数量,使得树脂固化成膜后,水相介质和醇类溶剂难以渗透进入聚合物中,从而提高了树脂涂层的耐水性和耐醇性。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer resin materials technology, specifically to the preparation and application of polyvinyl acetal resin with low metal ion content and high acetalization degree. Background Technology
[0002] With increasingly stringent environmental regulations, the printing industry is demanding more inks with low volatile organic compounds (VOCs). Increasing the solids content of inks is an effective way to reduce the use of organic solvents and lower VOC emissions. Polyvinyl acetal resin possesses good film-forming properties and pigment dispersibility, and is often used as a binder resin for inks. However, when formulating high-solids inks, conventional polyvinyl acetal resins can lead to an increase in the apparent viscosity of the ink system, resulting in poor ink flowability and making it difficult to meet the requirements of actual printing processes.
[0003] During the synthesis of polyvinyl acetal resin, neutralization with an alkaline aqueous solution is typically required after the acid-catalyzed reaction. This neutralization process generates inorganic metal salts, resulting in sodium, potassium, and calcium ions remaining within the resin. These metal ions undergo electrostatic adsorption or coordination with the polar hydroxyl groups on the resin molecular chains, forming physical crosslinks between polymer macromolecules. This physical crosslinking increases the resin's flow resistance in organic solvents, which is a major reason for the high viscosity of high-solids-content ink systems.
[0004] To reduce the viscosity of resin solutions to meet the requirements of high-solids inks, existing technologies typically employ methods to reduce the degree of acetalization. A lower degree of acetalization reduces steric hindrance in the molecular chains, which can decrease solution viscosity to some extent. However, a low degree of acetalization means that more hydrophilic hydroxyl groups remain on the resin backbone, leading to insufficient hydrophobicity after ink curing, decreased water and alcohol resistance of the coating, and a tendency to swell and whiten upon contact with water or alcohol solvents. Conversely, maintaining a high degree of acetalization directly to ensure coating resistance results in persistently high resin solution viscosity due to the cross-linking effect of residual metal ions. Currently, it is difficult to simultaneously achieve both the coating resistance and low viscosity flowability resulting from a high degree of acetalization in polyvinyl alcohol acetal resin systems. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides the preparation and application of polyvinyl alcohol acetal resin with low metal ion content and high acetalization degree. This solves the problem that existing polyvinyl alcohol acetal resins have high solution viscosity due to physical cross-linking caused by residual metal ions, making it difficult to simultaneously achieve the water and alcohol resistance properties brought by high acetalization degree and the low viscosity flowability required for preparing high solids inks.
[0006] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a polyvinyl acetal resin with low metal ion content and high acetalization degree, employing the following technical solution: A polyvinyl acetal resin with low metal ion content and high acetalization degree is prepared by reacting polyvinyl alcohol with an aliphatic aldehyde having 1 to 6 carbon atoms in an acid-catalyzed acetalization reaction and then eluting it with a treatment solution containing a weak acid; the degree of polymerization of the polyvinyl acetal resin is 150 to 800; the degree of acetalization of the polyvinyl acetal resin is 75% to 85%; and the total concentration of metal ions selected from at least one of sodium ions, potassium ions, calcium ions, and barium ions contained in the polyvinyl acetal resin does not exceed 80 ppm.
[0007] By employing the above technical solution, the degree of acetalization reaches 75% to 85% through an acid-catalyzed reaction between polyvinyl alcohol and aliphatic aldehydes with 1 to 6 carbon atoms. The numerous acetal ring structures provide hydrophobic side chains for the polymer backbone, improving the water resistance of the resin film. Simultaneously, the elution treatment using a weak acid solution removes residual sodium, potassium, calcium, and barium ions from the resin, reducing the total metal ion concentration to below 80 ppm. This eliminates the electrostatic adsorption or coordination between polyvalent or monovalent metal cations and the polar hydroxyl groups of the polymer chain, thus eliminating physical cross-linking nodes between molecules. Therefore, a resin product with low molecular chain entanglement density, low hydrodynamic frictional resistance, and low macroscopic apparent viscosity is obtained at a high solids content concentration.
[0008] Preferably, the polyvinyl alcohol acetal resin has a polyvinyl alcohol unit molar content of 10% to 25% and an acetyl unit molar content of 0.5% to 5%.
[0009] By adopting the above technical solution, retaining a specific proportion of polyvinyl alcohol units and acetyl units can maintain the basic polar sites of the resin molecules, improve the surface wetting ability and dispersion compatibility of the resin matrix to pigment particles, and at the same time limit the proportion of non-acetal units within the above range, it can ensure that the polymer as a whole exhibits a hydrophobic state, and prevent the coating from being eroded by aqueous media and causing swelling and whitening defects.
[0010] Secondly, the present invention provides a method for preparing a polyvinyl acetal resin with low metal ion content and high acetalization degree, using the following technical solution: The preparation of a polyvinyl acetal resin with low metal ion content and high acetalization degree includes the following steps: adding polyvinyl alcohol with a degree of polymerization of 150 to 800 and a degree of hydrolysis of 85% to 99% to deionized water, heating to 80°C to 95°C and maintaining the temperature with stirring until completely dissolved to obtain a polyvinyl alcohol aqueous solution; cooling the polyvinyl alcohol aqueous solution to 0°C to 30°C, adding an acid catalyst, and adding aliphatic aldehydes with 1 to 6 carbon atoms in portions to obtain a mixed system, wherein the molar ratio of the aliphatic aldehydes with 1 to 6 carbon atoms to the polyvinyl alcohol units is 0.6:1 to 1.2:1; the mixed system is first reacted at a constant temperature of 0°C to 30°C with stirring for 1 to 5 hours, and then the temperature is raised to 40°C to 70°C and the reaction continues for 2 to 6 hours to precipitate crude polyvinyl acetal resin; After the reaction was completed, the crude polyvinyl acetal resin was obtained by filtration. The crude polyvinyl acetal resin was washed with distilled water until the washing solution was neutral. The washed crude polyvinyl acetal resin was suspended in water to obtain a suspension system. An alkaline aqueous solution was added for neutralization until the pH value of the suspension system stabilized at 7 to 9. The neutralized polyvinyl acetal resin was obtained by filtration. The neutralized polyvinyl acetal resin is resuspended in a treatment solution containing a weak acid, wherein the weak acid is selected from at least one of acetic acid, formic acid, lactic acid, citric acid and tartaric acid, and the mass percentage of the weak acid is 0.5% to 5% of the dry weight of the polyvinyl acetal resin. The solution is then continuously stirred at 30°C to 60°C for 0.5 to 2 hours. After the treatment is completed, the treatment solution is filtered to obtain a weakly acid-treated polyvinyl alcohol acetal resin. The weakly acid-treated polyvinyl alcohol acetal resin is washed multiple times with deionized water until the conductivity of the filtered water after a single wash does not exceed 50 μS / cm. Finally, it is filtered and dried to obtain the polyvinyl alcohol acetal resin with low metal ion content and high acetalization degree.
[0011] By adopting the above technical solution, a process flow encompassing strong acid catalytic cyclization and multiphase weak acid elution was established, solving the technical problem of high viscosity caused by metal salt residue in the resin due to conventional neutralization processes. The specific reaction mechanism is as follows: The first stage is acetalization and ring formation. The aldehyde group of the aliphatic aldehyde and the adjacent polar hydroxyl group on the polyvinyl alcohol backbone undergo a condensation and dehydration reaction under the catalysis of hydrogen ions from the ionization of a strong acid, forming a hydrophobic acetal ring network, and the resin is precipitated.
[0012] In the second stage, metal ions are encapsulated. An alkaline aqueous solution is added for neutralization; the strong acid reacts with the alkali to form water-soluble inorganic salts. The generated metal ions are adsorbed onto the surface of the resin's polar groups or encapsulated within the resin's internal pores, forming physical cross-linking points that increase the solution's viscosity.
[0013] The third stage is proton exchange elution with a weak acid. Hydrogen ions provided by the weak acid in the elution solution diffuse into the resin interior driven by the concentration gradient, where they exchange ions with metal cations adsorbed on polyvinyl alcohol or acetyl units, displacing the metal cations into the aqueous phase. The weak ionization of the weak acid maintains a low hydrogen ion concentration, making the metal ion exchange process between the solid and liquid phases mild and controllable. If a strong acid were used directly for elution, on the one hand, the fully ionized high concentration of hydrogen ions might pose a potential risk to the thermodynamically unstable acetal ring structure, easily triggering irreversible ring-opening hydrolysis, thereby destroying the hydrophobic framework of the resin; on the other hand, the strong affinity of the acid radicals for the resin matrix makes them difficult to completely remove in subsequent washing processes, leaving residual acid radicals or salts as impurities, which would also lead to an abnormally high solution viscosity and degrade the coating performance.
[0014] This invention employs a weak acid system. The buffering properties of the weak acid maintain a stable low pH environment. This mild condition avoids the hydrolysis of the acetal ring that may be caused by high concentrations of strong acid, fundamentally circumventing the aforementioned multiple risks and ensuring the selectivity of the elution process and the purity of the final product. Accompanying the filtration and separation of the eluent, the displacement reaction continues in the direction of removing metal ions, ultimately removing the metal cations from the resin and dismantling the physical cross-linking network at the molecular level, thereby reducing viscosity.
[0015] Preferably, the acid catalyst is selected from either hydrochloric acid or sulfuric acid; the amount of acid catalyst added is measured by the ratio of the number of moles of hydrogen ions to the mass of polyvinyl alcohol in the mixed system, and the mass ratio of hydrogen ions to polyvinyl alcohol is from 5 mol / kg to 15 mol / kg.
[0016] By employing the above technical solution and limiting the feed ratio using hydrogen ions, the error in the effective catalytic proton quantity caused by selecting different types or concentrations of strong acid reagents is eliminated. An appropriate hydrogen ion concentration ensures that the acetalization dehydration process reaches the required activation energy conditions, thereby improving the cyclization substitution efficiency of aliphatic aldehydes.
[0017] Preferably, the alkaline aqueous solution is selected from either sodium carbonate aqueous solution or sodium hydroxide aqueous solution.
[0018] By adopting the above technical solution, the alkaline reagent can undergo a metathesis reaction with the residual free acid, preventing the acid from causing chain breakage and degradation of the macromolecular backbone during the drying and heating process.
[0019] Preferably, the treatment solution containing the weak acid includes a solvent selected from any one of deionized water, a mixture of water and ethanol, or a mixture of water and isopropanol.
[0020] By adopting the above technical solution, a mass transfer medium is provided for the acid-base reaction and subsequent proton elution and exchange reaction in the system.
[0021] Preferably, when the solvent is the water and ethanol mixture or the water and isopropanol mixture, the volume ratio of alcohol to water in the mixture is 1:4 to 3:7.
[0022] By employing the above technical solution, the resin achieving a high degree of acetalization exhibits hydrophobic characteristics, repelling the penetration of pure water and making it difficult for the internally encapsulated metal salts to contact the weak acids in the aqueous phase. Introducing alcohols allows the alcohol molecules to become compatible with the acetal resin, promoting the swelling of polymer particles and expanding the porosity between polymer chain segments. This provides a diffusion channel for the weak acids to penetrate deep into the resin and displace the metal salts, thereby improving the removal rate of metal ions.
[0023] Preferably, the treatment solution containing the weak acid also contains an organic complexing agent, which is selected from at least one of ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetic acid, and diethylenetriaminepentaacetic acid.
[0024] By employing the above technical solution, under the synergistic effect of swelling in alcohol solvents, the organic complexing agent, with its multi-coordination site structure, can complex with trace amounts of free metal cations eluted into the aqueous phase via proton exchange, forming stable water-soluble complexes. This complexing effect helps reduce the concentration of free cations in the liquid phase. According to the principle of chemical equilibrium shift, it can further promote the diffusion and removal of metal ions from the solid-phase resin into the liquid phase, thereby helping to control metal ion residues at a lower level.
[0025] Preferably, the degree of polymerization of the polyvinyl alcohol is 400, and the degree of hydrolysis of the polyvinyl alcohol is 98.5%; the solvent contained in the treatment solution containing the weak acid is a mixture of water and ethanol, the weak acid is acetic acid, and the organic complexing agent is disodium ethylenediaminetetraacetate; the mass percentage of acetic acid in the treatment solution is 1% of the dry weight of the polyvinyl alcohol acetal resin, and the volume ratio of alcohol to water in the mixture of water and ethanol is 1:4. The solution is continuously stirred at 50°C for 1 hour.
[0026] By adopting the above technical solution, raw materials with medium degree of polymerization and high degree of hydrolysis are combined with a specific alcohol-to-water ratio and weak acid concentration to balance the resin strength and swelling diffusion rate. Under specified heating and stirring conditions, the mass transfer efficiency of the ion replacement reaction reaches a high level, resulting in a product with good rheological properties.
[0027] Thirdly, this invention provides the application of low-metal-ion, high-acetalization-degree polyvinyl alcohol acetal resin in the preparation of high-solids-content, low-VOC inks, employing the following technical solution: Application of low-metal-ion, high-acetalization polyvinyl alcohol acetal resin in the preparation of high-solids, low-VOC inks, wherein the high-solids, low-VOC inks comprise the following components in parts by weight: 10 to 35 parts by weight of the polyvinyl alcohol acetal resin, 30 to 60 parts by weight of solvent, 10 to 30 parts by weight of pigment, and 0.5 to 10 parts by weight of additives; the solvent is selected from any one of anhydrous ethanol, isopropanol, and a mixture of ethanol and ethyl acetate with a water content not exceeding 5%; the solids content of the high-solids, low-VOC inks is not less than 25%, and the high-solids, low-VOC inks are tested at 25°C and a shear rate of 100 s. -1 The viscosity should not exceed 2000 mPa·s.
[0028] By employing the above technical solution, the prepared resin exhibits low intrinsic solubility viscosity due to its low metal cation crosslinking points and high proportion of hydrophobic acetal groups. Therefore, when formulated into ink, it maintains the overall low viscosity rheological properties of the system while achieving high solids content by increasing the resin addition and reducing the proportion of organic solvents, ensuring smooth printing. Simultaneously, the dried film matrix displays excellent optical smoothness and resistance to water and alcohol.
[0029] This invention provides the preparation and application of polyvinyl acetal resin with low metal ion content and high acetalization degree. It has the following beneficial effects: 1. This invention involves reacting polyvinyl alcohol with aliphatic aldehydes under acid catalysis to achieve an acetalization degree of 75% to 85% in the resin. The higher proportion of acetal structure increases the number of hydrophobic groups in the polymer chain, making it difficult for aqueous media and alcohol solvents to penetrate into the polymer after the resin is cured into a film, thereby improving the water resistance and alcohol resistance of the resin coating.
[0030] 2. In this invention, a treatment solution containing a weak acid is used for elution after the reaction. By utilizing the mild and controllable ion exchange characteristics of the weak acid system, the total concentration of residual metal ions in the resin is controlled to not exceed 80 ppm. The reduction of metal ions removes the physical cross-linking nodes between polymer chains caused by the combination of cations and polar hydroxyl groups, reduces the hydrodynamic resistance of the molecular chains in the solution, and thus reduces the apparent viscosity of the resin system in the organic solvent.
[0031] 3. The present invention applies the prepared low metal ion, high acetalization degree resin to ink formulation. Since the intrinsic solution of the resin has a low viscosity, the amount of organic solvent added can be effectively reduced when formulating ink. This allows the ink to achieve a high solid content to reduce the emission of volatile organic compounds while maintaining a low system viscosity, thus meeting the ink's fluidity and printing requirements. Detailed Implementation
[0032] The technical solutions of the present invention will be clearly and completely described below with reference to embodiments, comparative examples, and test examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0033] Examples 1-3: Example 1: This embodiment provides the preparation and application of polyvinyl acetal resin with low metal ion content and high acetalization degree, including the following steps: (1) Polyvinyl alcohol dissolution: Polyvinyl alcohol (degree of polymerization of 150 and degree of hydrolysis of 85%) is added to deionized water, heated to 80°C and kept warm with stirring until completely dissolved to obtain a uniform polyvinyl alcohol aqueous solution.
[0034] (2) Acetalization reaction: Cool the above polyvinyl alcohol aqueous solution to 0℃ and add hydrochloric acid as an acid catalyst (the amount of hydrochloric acid added is based on 5 mol H2O). + (Based on / kgPVA), then n-butyraldehyde (molar ratio of n-butyraldehyde to polyvinyl alcohol units is 0.6:1) is added in portions; the system is first stirred at 0℃ for 1 hour, then heated to 40℃ and reacted for another 2 hours to precipitate crude polyvinyl acetal resin.
[0035] (3) Neutralization and initial washing: After the reaction is completed, the crude resin is obtained by filtration. The crude resin is washed with distilled water until the washing liquid is neutral. The resin after initial washing is suspended in water and neutralized by adding 10% sodium carbonate aqueous solution until the pH of the suspension system is stable at 7.
[0036] (4) Low metal ionization treatment: The neutralized resin is resuspended in deionized water, acetic acid is added (the amount of acetic acid is 0.5% of the dry weight of the resin), and the mixture is stirred continuously at 30°C for 0.5 hours to perform metal ion replacement elution.
[0037] (5) Washing and drying: After the treatment is completed, the treatment solution is filtered to obtain the resin after weak acid treatment. The resin is washed multiple times with deionized water until the conductivity of the filtered water after a single wash is ≤50μS / cm. Finally, it is filtered and dried to obtain the target low metal ion, high acetalization degree polyvinyl alcohol acetal resin.
[0038] (6) Preparation of high solids content and low VOC ink: Weigh 10 parts by weight of the polyvinyl acetal resin prepared above, dissolve it in 30 parts by weight of anhydrous ethanol (water content ≤5%) and stir evenly; then add 10 parts by weight of pigment and 0.5 parts by weight of additives, add an appropriate amount of grinding media and vibrate and grind on a dispersion device to the specified fineness, filter to remove the grinding media, and the high solids content and low VOC ink is obtained. The solids content of the ink is not less than 25%, and it is heated at 25°C and a shear rate of 100s. -1 The viscosity should not exceed 2000 mPa·s.
[0039] Example 2: This embodiment provides the preparation and application of polyvinyl acetal resin with low metal ion content and high acetalization degree, including the following steps: (1) Polyvinyl alcohol dissolution: Polyvinyl alcohol (degree of polymerization of 400 and degree of hydrolysis of 98.5%) is added to deionized water, heated to 90°C and kept warm with stirring until completely dissolved to obtain a homogeneous polyvinyl alcohol aqueous solution.
[0040] (2) Acetalization reaction: Cool the above polyvinyl alcohol aqueous solution to 10°C and add hydrochloric acid as an acid catalyst (the amount of hydrochloric acid added is 8.5 mol H2). + (Based on / kgPVA), then n-butyraldehyde (molar ratio of n-butyraldehyde to polyvinyl alcohol units is 0.85:1) is added in portions; the system is first stirred at 10℃ for 2 hours, then heated to 60℃ and reacted for another 4 hours to achieve a degree of acetalization of more than 75%, and crude polyvinyl alcohol acetal resin is precipitated.
[0041] (3) Neutralization and initial washing: After the reaction is completed, the crude resin is obtained by filtration. The crude resin is washed with distilled water until the washing liquid is neutral. The resin after initial washing is suspended in water and neutralized by adding 10% sodium carbonate aqueous solution until the pH value of the suspension system is stable at 8.
[0042] (4) Synergistic treatment of low metal ionization: The neutralized resin is redispersed in a mixed solution of water and ethanol (the volume ratio of ethanol to water is 1:4), acetic acid (the amount of acetic acid is 1% of the dry weight of the resin) and an appropriate amount of organic complexing agent disodium ethylenediaminetetraacetate (EDTA-2Na) are added, and the mixture is continuously stirred at 50°C for 1 hour to achieve deep removal of metal ions by utilizing the synergistic effect of weak acid, alcohol and complexing agent.
[0043] (5) Washing and drying: After the treatment is completed, the treatment solution is filtered to obtain the resin after weak acid treatment. The resin is washed multiple times with deionized water until the conductivity of the filtered water after a single wash is ≤50μS / cm. Finally, it is filtered and dried to obtain the target low metal ion, high acetalization degree polyvinyl alcohol acetal resin.
[0044] (6) Preparation of high solids content and low VOC ink: Weigh 20 parts by weight of the polyvinyl acetal resin prepared above, dissolve it in 45 parts by weight of organic solvent (a mixture of ethanol and ethyl acetate, with a water content ≤5%) and stir evenly; then add 20 parts by weight of pigment and 5 parts by weight of additives, add an appropriate amount of grinding media and vibrate and grind on a dispersion device to the specified fineness, filter to remove the grinding media, and the high solids content and low VOC ink is obtained. The solids content of the ink is not less than 25%, and it is heated at 25°C and a shear rate of 100s. -1 The viscosity should not exceed 2000 mPa·s.
[0045] Example 3: This embodiment provides the preparation and application of polyvinyl acetal resin with low metal ion content and high acetalization degree, including the following steps: (1) Polyvinyl alcohol dissolution: Polyvinyl alcohol (degree of polymerization of 800, degree of hydrolysis of 99%) is added to deionized water, heated to 95°C and kept warm with stirring until completely dissolved to obtain a uniform polyvinyl alcohol aqueous solution.
[0046] (2) Acetalization reaction: The above polyvinyl alcohol aqueous solution was cooled to 30°C, and sulfuric acid was added as an acid catalyst (the amount of sulfuric acid added was 15 mol H₂). + (Based on / kgPVA), then n-butyraldehyde (molar ratio of n-butyraldehyde to polyvinyl alcohol units is 1.2:1) was added in portions; the system was first stirred at 30℃ for 5 hours, then heated to 70℃ and continued to react for 6 hours, precipitating crude polyvinyl alcohol acetal resin.
[0047] (3) Neutralization and initial washing: After the reaction is completed, the crude resin is obtained by filtration. The crude resin is washed with distilled water until the washing liquid is neutral. The resin after initial washing is suspended in water and neutralized by adding 10% sodium hydroxide aqueous solution until the pH value of the suspension system is stable at 9.
[0048] (4) Low metal ionization treatment: The neutralized resin is redispersed in a mixed solution of water and isopropanol (the volume ratio of isopropanol to water is 3:7), acetic acid is added (the amount of acetic acid is 5% of the dry weight of the resin), and the mixture is stirred continuously at 60°C for 2 hours to achieve deep removal of metal ions by utilizing the synergistic effect of weak acid and alcohol.
[0049] (5) Washing and drying: After the treatment is completed, the treatment solution is filtered to obtain the resin after weak acid treatment. The resin is washed multiple times with deionized water until the conductivity of the filtered water after a single wash is ≤50μS / cm. Finally, it is filtered and dried to obtain the target low metal ion, high acetalization degree polyvinyl alcohol acetal resin.
[0050] (6) Preparation of high solids content and low VOC ink: Weigh 35 parts by weight of the polyvinyl acetal resin prepared above, dissolve it in 60 parts by weight of isopropanol (water content ≤5%) and stir evenly; then add 30 parts by weight of pigment and 10 parts by weight of additives, add an appropriate amount of grinding media and vibrate and grind on a dispersion device to the specified fineness, filter to remove the grinding media, and the high solids content and low VOC ink is obtained. The solids content of the ink is not less than 25%, and it is heated at 25°C and a shear rate of 100s. -1 The viscosity should not exceed 2000 mPa·s.
[0051] Comparative Examples 1-4: Comparative Example 1: Compared with Example 2, the difference is that the low metal ionization synergistic treatment step (4) is omitted. That is, after the initial washing in step (3), the process directly proceeds to step (5) for fine washing and drying. The rest are the same.
[0052] Comparative Example 2: Compared with Example 2, the difference is that the amount of n-butyraldehyde used in step (2) is greatly reduced and the time of the high temperature reaction stage is shortened to 2 hours. The final resin acetalization degree is only 68% (failing to meet the 75% to 85% high acetalization degree required by the present invention), while the rest are the same.
[0053] Comparative Example 3: Compared with Example 2, the difference is that no ethanol or complexing agent (EDTA-2Na) was added to the low metal ionization synergistic treatment solution in step (4). Only acetic acid was added to the pure water system for treatment. All other aspects are the same.
[0054] Comparative Example 4: Compared with Example 2, the difference is that in step (4), the weak acid (acetic acid) is replaced with hydrochloric acid (strong acid), and the amount is controlled so that the pH value of the treatment solution is the same as that in Example 2, and the rest are the same.
[0055] Test Examples 1-4: Test Example 1: Weigh a dried resin sample that has undergone constant weight treatment and place it in a volumetric flask. Add a specified volume of solvent to completely dissolve the resin, preparing an extremely dilute polymer solution. Transfer the solution and pure solvent separately into an Orthocriteus viscometer in a constant temperature water bath and record the outflow time of the pure solvent and the resin solution under the same conditions. Calculate the relative viscosity and specific viscosity based on the outflow time ratio. Use extrapolation to determine the intrinsic viscosity of the system, and then substitute it into the Mark-Houwink empirical equation to calculate the actual average degree of polymerization of the resin.
[0056] A measured amount of resin sample was placed in an Erlenmeyer flask equipped with a reflux condenser. A mixture of pyridine and acetic anhydride was added, and the mixture was heated to allow for complete acetylation. After the reaction was terminated, distilled water was added to hydrolyze excess acetic anhydride into acetic acid. Using phenolphthalein as an indicator, the free acetic acid in the system was neutralized and titrated with a sodium hydroxide standard titration solution of known and accurate concentration. A blank test without resin sample was performed simultaneously. Based on the difference in the volume of sodium hydroxide solution consumed in the two titrations, the molar percentage of unreacted hydroxyl groups on the resin macromolecular chain was calculated, i.e., the polyvinyl alcohol unit content.
[0057] Accurately weigh another portion of the resin sample and add it to an Erlenmeyer flask. After dissolving it in neutral methanol, add a measured amount of sodium hydroxide standard solution and carry out the saponification reaction under reflux conditions. After the system cools, add phenolphthalein indicator and back-titrate the residual alkali using a standard concentration of sulfuric acid or hydrochloric acid titration solution, while simultaneously performing a blank test. Calculate the residual acetyl unit content in the resin based on the volume of standard acid consumed.
[0058] Based on the principle of chain segment conservation in polymer reactions, the total number of structural units in the resin system is set to 100%. The content of polyvinyl alcohol units and acetyl units obtained by titration is subtracted from this, and the remaining molar percentage is determined as the actual degree of acetalization.
[0059] Experimental data: Table 1. Test results of the basic structural parameters of the resins prepared in Examples 1-3 Note: The total content of the three units is 100%.
[0060] in conclusion: According to the data in Table 1, the actual test indicators of Examples 1 to 3 all fell within the set parameter range. The measured degrees of polymerization were 147, 391, and 784, respectively, which are basically consistent with the basic degree of polymerization of the raw material polyvinyl alcohol. This indicates that during the strong acid catalytic condensation and subsequent weak acid synergistic elution process, no obvious chain breaking or degradation side reactions occurred in the polymer backbone. This multiphase elution process is chemically inert to the carbon-carbon backbone.
[0061] The measured degrees of butyralization were 76.3%, 81.2%, and 84.6%, all consistently exceeding the design limit of 75%. With increasing catalyst concentration and temperature gradient in the reaction system, the thermodynamic process of cyclization between n-butyraldehyde and adjacent hydroxyl groups on the polyvinyl alcohol chain was effectively advanced, resulting in the conversion of a large number of hydrophilic polyvinyl alcohol units into hydrophobic six-membered acetal ring structures. The residual polyvinyl alcohol units on the macromolecular chain were compressed to the range of 14.2% to 21.8%, while the original acetyl units remained at a low level.
[0062] The convergence of the above data verifies the feasibility of the target product configuration design and explains the intrinsic mechanism that the subsequent deionization process must introduce a synergistic swelling mechanism from the molecular structure level. Due to the extremely high degree of acetalization of the measured product, the polymer matrix exhibits strong hydrophobic properties, with the free volume and capillary pores within the matrix occupied by nonpolar aliphatic side chains (butyl). Conventional pure aqueous solvents struggle to overcome surface tension to wet and penetrate the resin, and free hydrogen ions in the aqueous phase have difficulty contacting the encapsulated metal salt. Component analysis results demonstrate that the polar hydroxyl sites on the resin backbone have been significantly reduced, objectively requiring the use of alcohol solvents with similar miscibility characteristics in post-treatment. This opens the physical entanglement between hydrophobic segments and expands mass transfer channels, thereby enabling deep proton exchange and metal ion elution.
[0063] Test Example 2: A certain mass of dried resin sample was weighed and placed in a platinum crucible. It was slowly heated until completely carbonized, then transferred to a high-temperature muffle furnace and ignited until completely ashed. The crucible was removed and cooled to room temperature. A mixture of nitric acid and perchloric acid was added dropwise to the residue for digestion. After digestion, the clear solution was transferred to a volumetric flask and diluted to volume with deionized water.
[0064] A series of standard solutions for sodium, potassium, calcium, and barium were prepared, and the absorbance of each element was measured at its characteristic wavelength using a flame atomic absorption spectrometer to establish concentration-absorbance standard curves. Subsequently, the digested sample solution was analyzed using the spectrometer, and the detection concentration of each metal ion was calculated based on the standard curves. The total concentration of metal ions was then calculated by summing these values.
[0065] Accurately weigh the resin sample and slowly add it to a sealed glass container filled with anhydrous ethanol, controlling the resin mass fraction to be 20%. Use a high-shear disperser to mechanically stir and disperse the solid-liquid mixture at the set speed until the resin particles are completely dissolved, forming a homogeneous polymer solution without visible gel lumps.
[0066] The prepared polymer solution was transferred to a 25°C constant temperature water bath and allowed to stand until the system reached thermal equilibrium and all air bubbles trapped by stirring were expelled. A rotational viscometer was used to measure the viscosity at 100 s⁻¹. -1 The apparent viscosity of the solution was determined at the shear rate, and the rheological data were recorded after the instrument pointer or reading stabilized.
[0067] Experimental data: Table 2. Test results of metal ion concentration and solution viscosity in resins in Examples 1-3 in conclusion: According to the data in Table 2, the total metal ion concentrations of the resins prepared in Examples 1 to 3 were 74.24 ppm, 38.61 ppm, and 47.38 ppm, respectively, with corresponding 20% ethanol solution viscosities of 95.4 mPa·s, 68.7 mPa·s, and 82.1 mPa·s. All the indicators for each example met the set range of total metal ion concentration ≤ 80 ppm and solution viscosity ≤ 100 mPa·s. Combining the data in Tables 1 and 2, it can be seen that the measured degree of polymerization of Examples 1-3 treated with the weak acid system of this invention is basically consistent with the degree of polymerization of the feed, indicating that the entire elution process did not cause significant degradation to the main chain structure of polyvinyl acetal. At the same time, the metal ion concentration was effectively controlled, and the solution viscosity was significantly reduced. The weak acid treatment achieved efficient ion exchange while perfectly preserving the target molecular structure of the resin. In contrast, Comparative Example 4, treated with a strong acid, showed a comprehensive disadvantage in macroscopic performance, which indirectly confirms the negative impact of the strong acid system on the resin structure or purity.
[0068] Observation of ion distribution characteristics shows that sodium ions account for the majority of the metal residue in each embodiment, originating from the residual salts generated by the reaction of alkaline reagents and strong acids during the neutralization step. Different post-treatment process parameters directly affect the elution efficiency. Example 1 uses a single-phase elution system of pure water and weak acid. Due to the strong hydrophobic barrier of the high acetalized resin hindering proton penetration, its total metal ion concentration approaches the upper limit of control. Examples 2 and 3 introduce low-carbon alcohols into the eluent. The swelling effect of alcohol molecules expands the micropores and free volume inside the polymer, enabling the weak acid aqueous solution to have mass transfer channels to contact and displace deeply encapsulated salts. Further analysis of the data differences between Examples 2 and 3 shows that Example 2, which simultaneously introduces ethanol and an organic complexing agent (EDTA-2Na) into the eluent, has a significantly lower total metal ion concentration (38.61 ppm) than Example 3 (47.38 ppm, using only isopropanol, without adding a complexing agent). Although the difference may also be related to the type and amount of alcohol and the treatment temperature, in a weak acid treatment system containing low-carbon alcohols, the introduction of complexing agents tends to have a positive influence on the ion removal depth. By forming highly stable water-soluble complexes with free cations in the aqueous phase, complexing agents can effectively reduce the thermodynamic driving force for the re-adsorption of metal ions back to the resin solid phase.
[0069] Test data verified a strong positive correlation between polymer solution viscosity and metal ion concentration. Under conventional conditions without effective removal of metal ions, polyvalent or monovalent cations undergo ionic, dipole electrostatic adsorption, or coordination bonding with polar hydroxyl or acetyl groups on the polymer chains. This bonding constructs a physical cross-linking network between molecules in the solution state, increasing the entanglement density and hydrodynamic resistance of the polymer chains. After cation exchange via protons provided by a weak acid, the adsorbed metal ions are stripped to the liquid phase and eluted, and the non-covalent cross-linking points within the polymer matrix are completely deconstructed. As the metal ion concentration decreases sequentially, the steric hindrance and interchain friction of the polymer chain segments in the solution decrease simultaneously. Therefore, even at high concentrations with a solid content as high as 20%, the system can still overcome rheological hindrance, and its macroscopic shear stress and viscosity are reduced to extremely low levels unattainable by conventional resins. Blocking physical cross-linking through multiphase synergistic elution is an effective chemical mechanism for achieving intrinsic viscosity reduction in high acetalization resins.
[0070] Test Example 3: Prepare clean and constant-weight glass petri dishes, and accurately weigh the petri dishes using an analytical balance. Add the prepared ink samples to each petri dish separately, recording the total mass containing the sample to determine the initial ink mass. Place the petri dishes containing the samples in a preheated oven at 105°C and heat until the organic solvent has completely evaporated. Remove and cool to room temperature in a desiccator, then weigh again. Calculate the mass fraction of non-volatile substances in the system using the mass difference before and after heating, thus confirming the actual solid content.
[0071] The ink sample to be tested was transferred into the sample cup of the coaxial cylindrical rheometer, and the circulating water bath system was started to maintain the test environment temperature at 25°C. The system was allowed to stand until the sample reached thermal equilibrium. The shear rate of the test program was set to a constant value of 100 s. -1 Start the rotor to apply shear stress, and after the data acquisition curve of the torque sensor shows a plateau period, read and record the apparent viscosity value of the system.
[0072] Experimental data: Table 3. Test results of ink solid content and apparent viscosity in the examples and comparative examples in conclusion: According to the data in Table 3, the actual solid content of Examples 1 to 3 is distributed in the range of 28% to 32%, which meets the test standard of high solid content of ink greater than 25%. At the same solid content level, the apparent viscosity is effectively controlled in the range of 1254 to 1872 mPa·s, which is lower than the flowability threshold index of 2000 mPa·s. This verifies that the high acetalization degree resin after weak acid synergistic elution process has low shear stress response characteristics in dense particulate dispersion system.
[0073] Comparing the data of the examples and Comparative Example 1, Comparative Example 1, which did not undergo any metal ion removal process, had an ink viscosity as high as 3856 mPa·s. The unwashed resin retained a high concentration of inorganic salt groups, with free and adsorbed polyvalent and monovalent metal cations binding to polar sites on the polymer backbone. In formulations with increased solid content, the spatial distance between resin macromolecules is compressed. This ionic dipole interaction forms numerous physical cross-linking nodes between molecular chains, directly increasing the hydrodynamic resistance in the liquid phase and leading to loss of flowability at high solid content.
[0074] Comparative Example 3, using only pure water for elution, achieved a final apparent viscosity of 2463 mPa·s, failing to meet the test qualification standard. This rheological obstacle stemmed from insufficient elution depth. The highly acetalized resin exhibits strong hydrophobic properties, making it difficult for pure water, as a highly polar solvent, to wet and penetrate the internal pores of the resin particles. In this state, the protons released by the weak acid can only replace the metal ions on the particle surface; the internally encapsulated salts remain, demonstrating the necessity of introducing low-carbon alcohols as swelling agents in the post-treatment system to expand mass transfer channels and assist the proton exchange mechanism.
[0075] In Comparative Example 4, the eluent was changed to a strong acid system, and its measured viscosity increased to 2214 mPa·s. Subsequent tests showed that the coating gloss and alcohol resistance both deteriorated. These results indicate that a strong acid system is unsuitable for the post-treatment of the high acetalization degree resin of this invention. The reasons for the viscosity rebound and performance degradation are speculated to be twofold: First, the complete ionization of strong acids leads to excessively high local acidity in the system, which may induce hydrolysis and ring-opening side reactions of the acetal ring, thereby partially destroying the original surface affinity between the resin and the dispersed pigment, causing pigment particle aggregation or phase separation. Second, strong acid anions have strong physical adsorption or binding forces with the resin matrix, which are difficult to completely remove in subsequent conventional water washing processes. Residual acid or salt substances may catalyze side reactions or have adverse effects with additives in the system during resin drying or ink formulation, thereby causing an abnormal increase in the macroscopic rheological viscosity of the system. This, in turn, confirms that using weak acids to establish a mild and dynamic proton exchange balance mechanism is a necessary process boundary for achieving efficient desalination and minimizing the negative impact on the overall performance of the resin.
[0076] The viscosity of Comparative Example 2 was measured at 1185 mPa·s, which meets the flowability requirements. However, this low viscosity characteristic is based on a molecular basis with an acetalization degree of only 68%. The low density of hydrophobic side chains corresponds to less steric hindrance and lower intrinsic viscosity, avoiding the high frictional resistance caused by high acetalization, which is not within the scope of rheological interference caused by high substitution degree that needs to be addressed in this system.
[0077] Test Example 4: The inks were uniformly dispersed and applied to degreased tinplate and glass test plates using a bar coater, ensuring consistent wet film thickness. The coated samples were then placed in a constant temperature and humidity chamber and allowed to dry for 24 hours at 25°C and 50% relative humidity, allowing the organic solvents to evaporate completely and the polymer matrix to solidify into a film.
[0078] A smooth, defect-free coating sample was placed on a horizontal testing platform. Using a gloss meter, with the test geometry set to 60°, five different test points were selected on the surface of each sample to measure reflectance. After removing extreme values, the arithmetic mean of the gloss of each group of coatings was calculated.
[0079] A sample of coated tinplate with paraffin-sealed edges was taken and completely immersed in a deionized water bath maintained at 25°C. After immersion for 24 hours, the sample was removed and the surface moisture was blotted dry with filter paper. The macroscopic morphology of the coating surface was observed under natural light, and the occurrence of blistering, peeling, whitening, or loss of gloss was recorded and evaluated.
[0080] The sample coated on a glass plate is fixed on the test platform of a mechanical solvent-resistant wiping instrument. A standard degreased cotton ball is wrapped around the test probe, absorbing a specified volume of anhydrous ethanol reagent. The probe load is set to 500g, and a fixed-stroke reciprocating rubbing motion is performed on the coating surface. The number of wiping strokes is recorded when the coating surface shows signs of underlying layer exposure or large-area damage. If no damage is observed after 50 strokes, the test is stopped and recorded as passed.
[0081] Experimental data: Table 4. Test results of the overall performance of ink coatings in the examples and comparative examples. in conclusion: According to the data in Table 4, the 60° gloss of the ink coatings in Examples 1 to 3 ranged from 74.6% to 77.3%. After immersion in water for 24 hours, there was no change in macroscopic morphology, and no substrate exposure was observed after 50 repeated wipings with anhydrous ethanol. This indicates that after maintaining a high degree of acetalization and removing metal ions, the polyvinyl alcohol acetal resin, as a film-forming matrix, exhibits high stability and optical uniformity. The low-metal-ion environment dissolved the non-covalent crosslinking between resin chains, allowing the polymer segments to freely expand during solvent evaporation. This improved the resin's wetting and coating of pigment particles, resulting in a smooth and dense coating surface, reduced diffuse light reflection, and maintained high gloss levels.
[0082] Compared to the data in Comparative Example 1, the gloss of the untreated system decreased to 63.2%, and damage occurred during the 28th alcohol wiping. The strong ion-dipole interaction between the high concentration of metal ions and polar groups triggered localized micro-shrinkage of the polymer network during the film-forming and drying stage. This hindered the uniform compatibility between the resin macromolecules and pigments, leading to micro-phase separation and surface roughness, which macroscopically manifested as film haze and gloss degradation. Simultaneously, this electrostatically dependent physical cross-linking network was highly susceptible to swelling and disintegration under the penetration of strongly polar solvents (anhydrous ethanol), resulting in loss of coating cohesion and mechanical peeling.
[0083] The test sample in Comparative Example 2 exhibited severe whitening and blistering during the water resistance test. This system employed a strategy of reducing the degree of acetalization (68%) in exchange for low viscosity, resulting in a large number of unreacted free hydroxyl groups remaining on the polymer backbone. These polar groups have a very strong hydrogen-bonding affinity for water molecules, allowing the aqueous phase to easily penetrate and permeate the free volume within the polymer, causing volume swelling of the coating and altering the local refractive index, thus producing whitening. This performance demonstrates that maintaining a high degree of acetalization (above 75%) is crucial for achieving hydrophobic sealing of the coating in this system to resist aqueous media erosion.
[0084] In Comparative Example 4, after strong acid replacement, the gloss decreased to 61.4%, and large-scale peeling occurred after only 17 alcohol wiping cycles. The strong acid environment caused irreversible ring-opening and cleavage reactions of the six-membered acetal rings on the polymer backbone, leading to the disintegration of the original hydrophobic carbon chain network. The shortened chain byproducts and regenerated polar sequences severely weakened the mechanical strength and substrate adhesion of the coating. This verifies that using a weak acid to establish a mild and dynamic proton exchange balance mechanism is a necessary process boundary to prevent the overall degradation of the resin's physicochemical properties.
Claims
1. A polyvinyl acetal resin with low metal ion content and high acetalization degree, characterized in that, The polyvinyl alcohol acetal resin is prepared by reacting polyvinyl alcohol with aliphatic aldehydes having 1 to 6 carbon atoms in an acetalization reaction under acid catalysis and then eluting it with a treatment solution containing a weak acid. The degree of polymerization of the polyvinyl alcohol acetal resin is 150 to 800. The degree of acetalization of the polyvinyl alcohol acetal resin is 75% to 85%; The total concentration of metal ions selected from at least one of sodium, potassium, calcium and barium ions contained in the polyvinyl acetal resin does not exceed 80 ppm.
2. The resin according to claim 1, characterized in that, The polyvinyl acetal resin contains 10% to 25% polyvinyl alcohol units in a molar content of 0.5% to 5% acetyl units.
3. Preparation of polyvinyl acetal resin with low metal ion content and high acetalization degree, characterized in that, The preparation of a high degree of acetalization polyvinyl alcohol acetal resin according to any one of claims 1-2 comprises the following steps: Polyvinyl alcohol with a degree of polymerization of 150 to 800 and a degree of hydrolysis of 85% to 99% is added to deionized water, heated to 80°C to 95°C and kept at that temperature with stirring until it is completely dissolved to obtain a polyvinyl alcohol aqueous solution. The polyvinyl alcohol aqueous solution is cooled to 0°C to 30°C, an acid catalyst is added, and aliphatic aldehydes with 1 to 6 carbon atoms are added in portions to obtain a mixed system. The molar ratio of the aliphatic aldehydes with 1 to 6 carbon atoms to the polyvinyl alcohol units is 0.6:1 to 1.2:
1. The mixed system is first reacted at a constant temperature of 0°C to 30°C with stirring for 1 to 5 hours, and then the temperature is raised to 40°C to 70°C to continue the reaction for 2 to 6 hours, precipitating crude polyvinyl alcohol acetal resin. After the reaction was completed, the crude polyvinyl acetal resin was obtained by filtration. The crude polyvinyl acetal resin was washed with distilled water until the washing solution was neutral. The washed crude polyvinyl acetal resin was suspended in water to obtain a suspension system. An alkaline aqueous solution was added for neutralization until the pH value of the suspension system stabilized at 7 to 9. The neutralized polyvinyl acetal resin was obtained by filtration. The neutralized polyvinyl acetal resin is resuspended in a treatment solution containing a weak acid, wherein the weak acid is selected from at least one of acetic acid, formic acid, lactic acid, citric acid and tartaric acid, and the mass percentage of the weak acid is 0.5% to 5% of the dry weight of the polyvinyl acetal resin. The solution is then continuously stirred at 30°C to 60°C for 0.5 to 2 hours. After the treatment is completed, the treatment solution is filtered to obtain a weakly acid-treated polyvinyl alcohol acetal resin. The weakly acid-treated polyvinyl alcohol acetal resin is washed multiple times with deionized water until the conductivity of the filtered water after a single wash does not exceed 50 μS / cm. Finally, it is filtered and dried to obtain the polyvinyl alcohol acetal resin with low metal ion content and high acetalization degree.
4. The preparation method according to claim 3, characterized in that, The acid catalyst is selected from either hydrochloric acid or sulfuric acid; The amount of acid catalyst added is measured by the ratio of the number of moles of hydrogen ions to the mass of polyvinyl alcohol in the mixed system, and the mass ratio of hydrogen ions to polyvinyl alcohol is 5 mol / kg to 15 mol / kg.
5. The preparation method according to claim 3, characterized in that, The alkaline aqueous solution is selected from either sodium carbonate aqueous solution or sodium hydroxide aqueous solution.
6. The preparation method according to claim 3, characterized in that, The treatment solution containing a weak acid includes a solvent selected from any one of deionized water, a mixture of water and ethanol, or a mixture of water and isopropanol.
7. The preparation method according to claim 6, characterized in that, When the solvent is selected as the water and ethanol mixture or the water and isopropanol mixture, the volume ratio of alcohol to water in the mixture is 1:4 to 3:
7.
8. The preparation method according to claim 6, characterized in that, The treatment solution containing a weak acid also contains an organic complexing agent, which is selected from at least one of ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetic acid, and diethylenetriaminepentaacetic acid.
9. The preparation method according to claim 8, characterized in that, The degree of polymerization of the polyvinyl alcohol is 400, and the degree of hydrolysis of the polyvinyl alcohol is 98.5%. The treatment solution containing a weak acid contains a solvent that is a mixture of water and ethanol, the weak acid is acetic acid, and the organic complexing agent is disodium ethylenediaminetetraacetate. The acetic acid accounts for 1% of the dry weight of the polyvinyl acetal resin, and the volume ratio of alcohol to water in the water and ethanol mixture is 1:
4. The mixture is continuously stirred at 50°C for 1 hour.
10. The application of the low-metal-ion, high-acetalization polyvinyl alcohol acetal resin according to any one of claims 1 or 9 in the preparation of high-solids, low-VOC inks, characterized in that, The high-solids, low-VOC ink comprises the following components in parts by weight: The polyvinyl acetal resin comprises 10 to 35 parts by weight, a solvent comprises 30 to 60 parts by weight, a pigment comprises 10 to 30 parts by weight, and an additive comprises 0.5 to 10 parts by weight. The solvent is selected from any one of anhydrous ethanol, isopropanol, and a mixture of ethanol and ethyl acetate with a water content not exceeding 5%. The high-solids, low-VOC ink has a solids content of not less than 25%, and the high-solids, low-VOC ink is used at 25°C and a shear rate of 100 s. -1 The viscosity should not exceed 2000 mPa·s.